Effectiveness of physiotherapist-led exercise interventions for burn rehabilitation: A systematic review and meta-analysis. - Ulric Sena Abonie; Martin Ackah; Tapfuma Mudawarima; Alberta Rockson (PLoS ONE)
Background Exercise is utilised by physiotherapists to prevent complications and improve overall function and quality of life post-burn. However, the effect of physiotherapist-led exercise has not been comprehensively reviewed. Consequently, this study aimed to investigate the effectiveness of physiotherapy exercises for persons' post-burn. Methods PubMed, CINAHL, Cochrane Library, and Web of Science were searched from database inception to September 27, 2024, to identify relevant studies. Two independent reviewers screened and selected the articles. Studies were included if they were randomised controlled trials of physiotherapy exercises to improve functional outcomes in persons with post burn injuries. Extracted data included author's surname and year, country, population type, sample size, age, and total body surface area, mode, frequency and duration of exercise. The quality of the evidence was assessed with the Cochrane risk of bias (RoB 2.0) tool. Narrative synthesis and meta-analysis were conducted to examine exercise effect on physical, physiological and psychological outcomes. Results Out of 3610 records screened, eight articles involving 393 participants were deemed eligible for inclusion. Physiotherapy exercises significantly improved lean body mass and pulmonary function but did not improve quality of life. Meta-analysis showed significant effects for aerobic capacity (Hedge's g = 1.13, 95% confidence interval: 0.44-1.83, p = 0.00) and muscle strength (Hedge's g = 2.27, 95% confidence interval: 0.42-4.13, p = 0.02). Conclusion Physiotherapy exercises have positive impacts on physical, physiological and psychological outcomes particularly aerobic capacity and muscle strength in individuals' post burns. The heterogeneity in effects for all outcomes highlights the need for further research.